SAT0004 Increased Levels of Thrombin Activatable Fibrinolysis Inhibitor - TAFI Correlate with Complement Activation in Patients with the Antiphospholipid Syndrome. (10th June 2014) - Antovic, A.; Vikerfors, A.; Woodhams, B.; Adam, M.; Svenungsson, E.
Abstract : Background: The Antiphospholipid syndrome (APS) is diagnosed when arterial/venous/small vessel thrombosis or obstetric morbidity occur together with positive laboratory tests for antiphospholipid antibodies (aPL, including anticardiolipin (aCL) and/or anti-β2 glycoprotein-I (a β2 GPI) and/or the functional lupus anticoagulant (LA) test). The pathophysiology behind aPL associated thrombosis is complex. Thrombin activatable fibrinolysis inhibitor (TAFI) represents a link between coagulation and fibrinolysis. Active form of the enzyme removes carboxyl-terminal lysine residues from partially degraded fibrin, thus maintaining fibrin clots and having a prothrombotic function. TAFI has been considered a potential acute phase protein while it may mediate anti-inflammatory effects by regulating complement anaphylatoxins C3a and C5a which are also of importance for the pathogenesis of APS. Objectives: To investigate TAFI levels in relation to the fibrin clot tightness and fibrinolytic function as well as complement activation in patients with APS. Methods: 50 patients with APS and 15 controls were included. The levels of pro-TAFI (proenzyme) and TAFIa/TAFIai (complex of active and inactive form which corresponds to the concentration of the active form that cannot be measured because of instability) were analyzed with a chromogenic assay for TAFI and a specific ELISA for TAFIa/ai (both from Diagnostica Stago, Asnieres, France). Fibrin permeability was assessed by flow measurement and clot lysis time (CLT) was analysed by a turbidimetric lysis assay. C5a was analysed by a specific ELISA (Becton Dickinson Bioscience, NJ, USA). Results: The levels of proenzyme - Pro-TAFI (%) as well as the levels of active enzyme TAFIa/TAFIai (ng/mL) were significantly increased in patients with APS compared to controls (114±2.7 vs 88.7±16.5; p<0.001 and 18.9±1.6 vs 12.2±0, 7; p<0.001, respectively). Fibrin permeability expressed as permeability coefficient Ks (cm 2 x10 -9 ) was lower in samples from APS-patients compared to controls (6.4±0.6 vs 9.8±0.8; p<0.001) indicating a tighter fibrin structure. CLT (seconds) was longer in APS-samples compared to controls (374±34.3 vs 278±42.2; p<0.001, respectively). TAFI levels did not correlate with CLT, neither with Ks in the investigated samples. However, moderately significant correlation was found between pro-TAFI and C5a (r=0.37; p<0.01). Conclusions: Increased levels of TAFI-proenzyme were found in patients with APS as a potential response to increased complement activation. In spite of increased TAFI activation it does not seem that active form of TAFI significantly contributes to fibrinolysis impairment in APS. However further studies are required to elucidate TAFIs role in the pathophysiology of APS. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3908